1986
DOI: 10.1029/ja091ia03p03077
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic electron and energetic ion precipitation spikes near the plasmapause

Abstract: An investigation has been made of electron and associated ion precipitation spikes near the plasmapause that are narrow in L shell and in which relativistic electrons are favored. The electron energy spectra during the spikes sometimes had equivalent e fold energies in excess of 500 keV. In approximately 31% of these spike events observed from the low‐altitude polar orbiting satellites P72‐1, P78‐1, and S81‐1, nearly simultaneous precipitation was measured in energetic ions above ∼30 keV at about the same L va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 18 publications
3
61
1
Order By: Relevance
“…The preferential occurrence of REP on the duskside has been observed by both satellites [Vampola, 1971;Green et al, 2004;Carson et al, 2013;Comess et al, 2013] and balloons [Foat et al, 1998;Lorentzen et al, 2000;Millan et al, 2002]. Coincident precipitation of electrons and ions has been reported by various satellite studies [Imhof et al, 1986;Bortnik et al, 2006;Sandanger et al, 2009;Carson et al, 2013]. Storm Probes (RBSP, now called "the Van Allen Probes") mission, provides the first balloon measurements of REP while comprehensive in situ measurements of both plasma waves and energetic particles are available .…”
Section: Introductionmentioning
confidence: 99%
“…The preferential occurrence of REP on the duskside has been observed by both satellites [Vampola, 1971;Green et al, 2004;Carson et al, 2013;Comess et al, 2013] and balloons [Foat et al, 1998;Lorentzen et al, 2000;Millan et al, 2002]. Coincident precipitation of electrons and ions has been reported by various satellite studies [Imhof et al, 1986;Bortnik et al, 2006;Sandanger et al, 2009;Carson et al, 2013]. Storm Probes (RBSP, now called "the Van Allen Probes") mission, provides the first balloon measurements of REP while comprehensive in situ measurements of both plasma waves and energetic particles are available .…”
Section: Introductionmentioning
confidence: 99%
“…Some relativistic electron precipitation bursts, many of which were observed in the drift loss cone, were previously found to occur in the vicinity of the plasmapause position estimated from the K P index (Imhof et al, 1986). These bursts were predominantly in the L shell range of ∼ 4 to ∼ 7 and, therefore, probably near the trapping boundary.…”
Section: Observations Of Electron Beams In the Magnetospherementioning
confidence: 99%
“…According to Thorne and Kennel (1971) the presence of the proton precipitation is expected during the relativistic electron precipitation. But, as shown by Imhof et al (1986), localized precipitation of electrons from the inner part of the radiation belt correlates with the proton precipitation spikes only in 31% of the observed events.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes the precipitation was registered nearly simultaneously on board dierent satellites spaced tens of degrees in longitude apart. Duration of the relativistic electron precipitation bursts varies from <1 s to 10± 30 s (Imhof et al, 1986(Imhof et al, , 1991(Imhof et al, , 1992Nakamura et al, 1995) Thorne and Kennel (1971) suggested a mechanism for the relativistic electron precipitation in the evening and night sectors near the plasmapause. The precipitation from the radiation belt was thought to be related to the electromagnetic ion cyclotron waves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation